PEMAKAIAN PREBIOTIK UBI JALAR KUNING (Ipomoea batatas L) DAN PROBIOTIK Lactobacillus casei PADA PEMBUATAN SUSU FERMENTASI SINBIOTIK - FAJAR, NAJMIATUL; Indriati, Gustina (IAIN Batusangkar, 2010)
This research study about use of prebiotic Ipomea batatas L. and probiotic Lactobacillus casei at milk fermentation. The usage of simbiotic increase, recentely, especially, for husbandarys products, such as milk fermentation the purpose of this study was to find out the best composition of prebiotic Ipomoea batatas L and probiotic Lactobacillus casei given in the process of simbiotic milk fermentation. The method used for this experiment was random cluster, factorial 4 x 3 with 3 times of re-treatment, and was analyzed with BNT and BNJ testing. ?A? factor was the use of prebiotic Ipomoea batatas L. (0%, 7,5 %, 15 %, 22,5 %), and ?B? factor was the use of probiotic Lactobacillus casei (2%, 3%, 4 %) the component measure were BAL , water and TTA the result of this study was shown that the best use of prebiotic Ipomoea batatas L and probiotic Lactobacillus casei in the process of symbiotic milk fermentation were in the composition of highest BAL : 21,40 x 108 cfu/ml. the highest TTA and water were 0,21 % and 71,98 22,5 % of prebiotic Ipomoea batatas L. and 4% probiotic Lactobacillus casei consentrate. Key words: prebiotic, Ipomea batatas L., probiotic, Lactobacillus casei, milk fermentatio